Avaliação histopatológica de mamíferos marinhos encalhados no litoral do nordeste brasileiro - Brito, Ana Paula Domingos (Universidade Federal Rural do Semi-Árido, 2015)
Pathological examination of marine mammals carcasses is an important tool to understand the natural morphophysiology as well as the morphological changes associated with some diseases and thus highlight the potential anthropogenic impacts. This work had as aim conduct studies on histopathology of the organs of the dead stranded cetaceans and Sirenia in the Brazilian northeast coast, or that died during the rehabilitation process in Specialized Centers of the Region. For this, samples were taken belonging to the biological collection of Projeto Cetáceos da Costa Branca (PCCB), Associação de Pesquisa e Preservação de Ecossistemas Aquáticos (AQUASIS) and from Centro de Mamíferos Aquáticos (CMA). The tissue samples were submitted to the conventional method of preparing histological slides. Whereas the studied animals belong to different species, age and sex, a general descriptive analysis of the pathological aspects found in each case was carried out. From a total of 237 samples belonging to 66 individuals of the Cetacea order (n = 28) and Sirenia (n = 38), 34,17% (n = 81) exhibited microscopic changes, 54,85% (n = 130) were normal and 10,97% (n = 26) were autolysed. Among the obvious microscopic changes was diagnosed 50% of stomatitis in the oral system (n = 1), the heart showed 6.66% of interstitial fibrosis (n = 2), 10% of haemorrhage (n = 3) and 6.66% myocarditis (n = 2). The lungs showed pulmonary edema in 19% of the analyzes (n = 11), 10% of vascular congestion% (n = 6), 13% of haemorrhage (n = 8), 3% of emphysema (n = 2), 7% full of hemosiderin (n = 4), 3% of interstitial pneumonia (n = 2), 2% of eosinophilic pneumonia (n = 1), 2% of parasitic granuloma (n = 1), 2% of parasitic cyst (n = 1), 2% of traqueíte (n = 1). In the stomach was visualized a hemorrhage (16.66%; n = 1) and in the gut was detected nodular lymphoid hyperplasia (7%; n = 2), enteritis (4%; n = 1), blood vessels congestion (4%; n = 1) and vacuolar degeneration (4%; n = 1). The livers analysis showed 23% of vacuolar degeneration (n = 5), 9% of hepatocellular necrosis (n = 2), 9% moderate deposit of melanin granules (n = 2), 4.54 % of chronic hepatitis (n = 1), 9% of periportal fibrosis (n = 2), 4.54% of abscess (n = 1), 4.54% of congestion (n = 1), 4.54 % of bilestase (n = 1), and 4.54% proliferation of the bile ducts (n = 1). It was possible to observe in the spleen 20% white pulp rarefaction (n = 2), 10% white and red pulp rarefaction (n = 1), and 30% moderate deposition of melanin granules (n = 3). In the pancreas was observed a 50% of centroacinosas cells rarefaction (n = 1). In the kidneys was found 14% of toxix tube nephrosis (n = 4), 7% of multifocal hemorrhaging (n = 2), 14% of vascular congestion (n = 4), 3.44% presence of bacteria (n = 1), 3.44% of proliferative glomerulonephritis (n = 1), 3.44% of micro abscesses (n = 1), 3.44% of severe edema (n = 1), 3.44% of renal cysts (n = 1) and 3.44% of chronic interstitial nephritis (n = 1). In the uteri evaluated were observed 25% of a focal dystrophic calcification (n = 1) and 25% of metritis (n = 1). In the lymph nodes were observed suggestive abnormalities of immunosuppression (25%; n = 1), bleeding (25%; n = 1) and melanose (50%; n = 2). Other findings include rarefaction of the adrenal cells (50%, n = 1), fewer sperm cells into the lumen (14,28%; n = 2) or presence of only spermatogonia in the seminiferous tubules (21,42%; n = 3), and 25% focal hyperplasia of the bladder (n = 1). Despite the changes present in many systems, lung diseases were higher in cetaceans bodies and sirenians stranded on the Brazilian northeast coast
Marine mammals of assessment histopathological stranded in the brazilian northeast coast
Keywords: Cetacea and Sirenia; Marine mammals; Histopathology; Cetáceos e sirênios; Mamíferos marinhos; Histopatologia; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL